0.6x+1.5=-0.6(2x+5)

Simple and best practice solution for 0.6x+1.5=-0.6(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6x+1.5=-0.6(2x+5) equation:


Simplifying
0.6x + 1.5 = -0.6(2x + 5)

Reorder the terms:
1.5 + 0.6x = -0.6(2x + 5)

Reorder the terms:
1.5 + 0.6x = -0.6(5 + 2x)
1.5 + 0.6x = (5 * -0.6 + 2x * -0.6)
1.5 + 0.6x = (-3 + -1.2x)

Solving
1.5 + 0.6x = -3 + -1.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1.2x' to each side of the equation.
1.5 + 0.6x + 1.2x = -3 + -1.2x + 1.2x

Combine like terms: 0.6x + 1.2x = 1.8x
1.5 + 1.8x = -3 + -1.2x + 1.2x

Combine like terms: -1.2x + 1.2x = 0.0
1.5 + 1.8x = -3 + 0.0
1.5 + 1.8x = -3

Add '-1.5' to each side of the equation.
1.5 + -1.5 + 1.8x = -3 + -1.5

Combine like terms: 1.5 + -1.5 = 0.0
0.0 + 1.8x = -3 + -1.5
1.8x = -3 + -1.5

Combine like terms: -3 + -1.5 = -4.5
1.8x = -4.5

Divide each side by '1.8'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 | | 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 |

Equations solver categories